(untitled) (MAUSAM, 1983)
The wind field and 12-hourly change in absolute vorticity have been examined for a few rainstorm situations in the Bhagjrathj catchment one day in advance to the storm with a view to locating areas of positive vorticity changes as one of the criteria in conjuction with other meteorological parameters associated with synoptic types for forecasting rainfall over Bhagirathi catchment. Convergence patterns as revealed by positive vorticity changes over the area bounded by Lat. 21-26 N and Long. 84-92 E containing Bhagirathi catchment have been plotted and compared with the isohyetal patterns of observed rainfall at 03 GMT of the next day. The study shows that there is resemblance between the two patterns. It is suggested that the areas of positive total vorticity changes may be taken as a guide to forecast areas of precipitation 12 to 15 hours in advance keeping in view the likely lateral shift of the forecast areas of precipitation as judged by synoptic situation.